A split sex ratio in solitary and social nests of a facultatively social bee. (26th April 2019) - Smith, Adam R.; Kapheim, Karen M.; Kingwell, Callum J.; Wcislo, William T.
Abstract : A classic prediction of kin selection theory is that a mixed population of social and solitary nests of haplodiploid insects should exhibit a split sex ratio among offspring: female biased in social nests, male biased in solitary nests. Here, we provide the first evidence of a solitary–social split sex ratio, using the sweat bee Megalopta genalis (Halictidae). Data from 2502 offspring collected from naturally occurring nests across 6 years spanning the range of the M. genalis reproductive season show that despite significant yearly and seasonal variation, the offspring sex ratio of social nests is consistently more female biased than in solitary nests. This suggests that split sex ratios may facilitate the evolutionary origins of cooperation based on reproductive altruism via kin selection.